Analysis of scattered supernatant patterns in Tehran urban complex Emphasizing on the approaches of the urban management system - Sogand Yousefi azarabarghani; Hamid Majedi; Zahra Sadat Saeideh Zarabadi (تحقیقات کاربردی علوم جغرافیایی)
The growth and expansion of the dispersed development pattern is one of the ways of settlement development that is shaped by a variety of factors, including urban management policies and approaches. Examine how the development of Tehran's metropolitan area has evolved over the last fifty years and what effective urban management policies and approaches have been and how it has influenced city development. This article deals with it. This research has been used because of the importance of the topic in a descriptive-analytical and practical purpose, based on library and documentary studies and in some cases field observations. In order to achieve the objectives of the study, three types of measurement models were used depending on the subject and variables of the study. In this regard, physical continuity in Tehran urban complex through Shannon entropy model, functional continuity through network analysis model (investigation of habitat and flow points and distribution and land use composition) and poor urban slope growth using Helder model The measurement is located. The findings show that: 1) dispersal phenomena have occurred in Tehran metropolitan area (Helderen and Shannon entropy model), 2) Tehran metropolitan area has been experiencing functional divergence (network analysis) and user distribution The services and services at the Tehran metropolitan level have not been uniform and balanced; and 3) the policies and approaches of urban management in successive years have had wide-ranging effects on spatial dispersal and unbalanced spatial development. Tehran's urban complex had.